The gender dimensions of environmental change : an exploration of the experiences and perceptions of rural men and women in Zimbabwe : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies at Massey University, Manawatu, New Zealand - Shumba, Dorcas Stellah Tsitsi (Massey University, 2016)
Processes of environmental change have taken place for centuries both as a result of natural variability and anthropogenic forces. As a concept however, environmental change continues to be used narrowly to refer to environmental changes which are biophysical in nature, and mostly those with global precedence. In recent times incidences of environmental change have become more complex as new patterns of change are threatening the livelihoods of those living in developing countries, undoing many development gains. As such, there is an increasing desire to understand the implications of environmental changes, particularly for those whose livelihoods are natural resource dependent, many of whom live in rural areas, and many of whom are poor. Despite this growing interest, rural people and especially the rural poor are little seen or heard; their environmental change experiences are thus misunderstood, and solutions proposed do not take into consideration the local context or experiences. There remains also a normative perspective which positions women as automatically vulnerable to environmental change, specifically vis-à-vis men. In doing so women’s experiences of environmental change are homogenised and men’s experiences are rendered invisible. Drawing on the case of Zimbabwe this study critically considers the experiences and perceptions of rural men and women to environmental change so as to ascertain gendered impacts and differential vulnerabilities. To capture fully the subjective lived experience of both men and women to environmental change, this study lends itself to qualitative research. Thus research methods such as semi-structured interviews, focus group discussions and gender analysis are central to the methodology. In terms of findings, this study argues against looking at environmental change as a technocratic subject accessible only from a global frame and accessed only by a technocratic few, proposing that the people experiencing environmental change at a local level should determine the environmental changes of communal concern. This study also highlights the importance of understanding the vulnerabilities of rural men and women within a well-conceived notion of context, taking into account rural disadvantage resulting from colonialism, and the current Zimbabwean crisis.
Keywords: Climatic changes; Environmental aspects; Rural development; Women in development; Global environmental change; Environmental conditions; Zimbabwe; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Gender studies